2020
DOI: 10.3389/fimmu.2020.527310
|View full text |Cite
|
Sign up to set email alerts
|

LT-K63 Enhances B Cell Activation and Survival Factors in Neonatal Mice That Translates Into Long-Lived Humoral Immunity

Abstract: Adjuvants enhance magnitude and duration of immune responses induced by vaccines. In this study we assessed in neonatal mice if and how the adjuvant LT-K63 given with a pneumococcal conjugate vaccine, Pnc1-TT, could affect the expression of tumor necrosis factor receptor (TNF-R) superfamily members, known to be involved in the initiation and maintenance of antibody responses; B cell activating factor receptor (BAFF-R) and B cell maturation antigen (BCMA) and their ligands, BAFF, and a proliferation inducing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 70 publications
6
14
0
Order By: Relevance
“…Ab persistence is mediated by long-lived plasma cells that reside in specialized survival niches in the bone marrow ( 34 ) and their survival was recently shown to be dependent on direct contacts with stromal cells as well as APRIL : BCMA binding ( 35 ). In line with that, we demonstrated that LT-K63 enhanced early APRIL expression by bone marrow accessory cells, particularly by eosinophils, macrophages and megakaryocytes after immunization of neonatal mice with Pnc1-TT ( 15 ). Additionally, a higher proportion of plasmablasts and plasma cells of neonatal mice immunized with Pnc1-TT with LT-K63 expressed BCMA ( 15 ).…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Ab persistence is mediated by long-lived plasma cells that reside in specialized survival niches in the bone marrow ( 34 ) and their survival was recently shown to be dependent on direct contacts with stromal cells as well as APRIL : BCMA binding ( 35 ). In line with that, we demonstrated that LT-K63 enhanced early APRIL expression by bone marrow accessory cells, particularly by eosinophils, macrophages and megakaryocytes after immunization of neonatal mice with Pnc1-TT ( 15 ). Additionally, a higher proportion of plasmablasts and plasma cells of neonatal mice immunized with Pnc1-TT with LT-K63 expressed BCMA ( 15 ).…”
Section: Introductionsupporting
confidence: 86%
“…In line with that, we demonstrated that LT-K63 enhanced early APRIL expression by bone marrow accessory cells, particularly by eosinophils, macrophages and megakaryocytes after immunization of neonatal mice with Pnc1-TT ( 15 ). Additionally, a higher proportion of plasmablasts and plasma cells of neonatal mice immunized with Pnc1-TT with LT-K63 expressed BCMA ( 15 ). Therefore, we wanted to explore whether the difference we previously observed ( 20 ) in the persistence of humoral immune responses induced by the selected adjuvants could be explained by their different effects on expression of plasma cell survival factors by bone marrow accessory cells and BCMA expression of plasmablasts/plasma cells up to this 6 week time point, where LT-K63 is used as a positive control.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition to use of PAMPS that are likely to affect multiple immune populations, small molecules that bind B cell surface receptors involved in survival and proliferation, such as BAFF, APRIL, and soluble CD40L, have shown promise as potential adjuvants in adult models [ 169 ] ( Figure 2 ). However, the utility of these adjuvants in young infants may be limited by differences in expression of the surface receptors for these molecules [ 170 ]. This is exemplified by the diminished expression of TACI by B cells observed in newborn mice, leading to deficits in plasma cell differentiation even in the presence of exogenous BAFF and APRIL [ 47 ].…”
Section: Strategies To Increase the Effectiveness And Breadth Of Protection Conferred By Newborn Influenza Vaccinesmentioning
confidence: 99%